Democratic Citizenship Education and its Practices in Social Studies’ Classrooms at Elementary School Level - Kamran, Muhammad (Journal of Peace, Development and Communication, 2021)
The importance of democratic citizenship education in democratic states is beyond dispute. The general purpose of the study is to describe democratic citizenship education and its practices in social studies’ classrooms at elementary school level. The study is qualitative in nature and descriptive phenomenological research design is used for this study. The accessible population of the study is included all the social studies’ teachers of 83 boys’ public sector elementary schools in district Lahore. Purposive sampling is used for the selection of the sample in this study. The sample of the study is included 20 social studies’ teachers of 10 boys’ public sector elementary schools of district Lahore. Two social studies’ teachers, one from primary section (grade 1- 5) and one from elementary section (grade 6- 8) who are teaching social studies’ subjects are selected from 10 boys public sector elementary schools of district Lahore by using purposive sampling technique. Participant observation is adopted as a tool to observe classrooms of social studies teachers through a checklist of objectives. Data is analyzed by using SPSS (statistical package of social sciences) software. On the basis of results it is concluded that majority of the social studies’ teachers are emerging their competencies and need improvement regarding the development of democratic citizenship education at public sector elementary school level. Keywords: Democratic Citizenship, Democracy, Social Studies, Classrooms